Acceptability of silage from brown seaweed (lessonia trabeculata) by the red abalone (haliotis rufescens) in experimental conditions - Méndez Ancca, Sheda (2018)
The nutritional value during the preparation and conservation of the silage is still of great interest for human and animal consumption. The objective of the study was to demonstrate if the Red abalone (Haliotis rufescens) consumes the silage of Brown seaweed (Lessonia trabeculata) under experimental conditions, on the Morro Sama-Tacna FONDEPES aquaculture Centre, during the years 2017 and 2018. We experimented with the control group (fresh seaweed) and two types of silage, treatments: T1 (silage 0% on dry basis) and T2 (silage 35% on dry basis) for 62 days; determining the content of proteins, fats, carbohydrates and energy in the fresh seaweed, no statistically significant difference (p < 0.05) were observed between the treatments, except for the fat content. Treatments, food acceptance was observed during 10 days and food consumption, sizes and weights were estimated with statistically similar. It was concluded that the abalone eat silage and the highest percentages of bromatological composition corresponded to T2, its consumption to gain weight and height of Haliotis rufescens where probably these variables increase when there is a higher percentage of silage based on dry matter or more days of consumption. Microbiological analysis showed that the silages are suitable for the consumption of the species.